Current and future disease progression of the chronic HCV population in the United States. - Martin Zalesak (Public Library of Science (PLoS), 2013)
Chronic hepatitis C virus (HCV) infection can lead to advanced liver disease (AdvLD), including cirrhosis, decompensated cirrhosis, and liver cancer. The aim of this study was to determine recent historical rates of HCV patient progression to AdvLD and to project AdvLD prevalence through 2015. We first determined total 2008 US chronic HCV prevalence from the National Health and Nutrition Evaluation Surveys. Next, we examined disease progression and associated non-pharmacological costs of diagnosed chronic HCV-infected patients between 2007-2009 in the IMS LifeLink and CMS Medicare claims databases. A projection model was developed to estimate AdvLD population growth through 2015 in patients diagnosed and undiagnosed as of 2008, using the 2007-2009 progression rates to generate a "worst case" projection of the HCV-related AdvLD population (i.e., scenario where HCV treatment is the same in the forecasted period as it was before 2009). We found that the total diagnosed chronic HCV population grew from 983,000 to 1.19 million in 2007-2009, with patients born from 1945-1964 accounting for 75.0% of all patients, 83.7% of AdvLD patients, and 79.2% of costs in 2009, indicating that HCV is primarily a disease of the "baby boomer" population. Non-pharmacological costs grew from $7.22 billion to $8.63 billion, with the majority of growth derived from the 60,000 new patients that developed AdvLD in 2007-2009, 91.5% of whom were born between 1945 and 1964. The projection model estimated the total AdvLD population would grow from 195,000 in 2008 to 601,000 in 2015, with 73.5% of new AdvLD cases from patients undiagnosed as of 2008. AdvLD prevalence in patients diagnosed as of 2008 was projected to grow 6.5% annually to 303,000 patients in 2015. These findings suggest that strategies to diagnose and treat HCV-infected patients are urgently needed to increase the likelihood that progression is interrupted, particularly for patients born from 1945-1964.